PENGEMBANGAN KARIER PEGAWAI NON MEDIS (Studi Deskriptif Kualitatif di RSUD Dr. M. YUNUS BENGKULU) - Haryati Utami (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2018)
Haryati Utami; The purpose of this study is to describe the role of individuals, management roles and organizational roles towards career development of medical personnel in Dr. M. Yunus from Bengkulu. Data method used is observation, questioner and interview. The research was carried out by distributing questionnaires to 40 non medical personnel in Dr. M. Yunus from Bengkulu. In this study also interviewed 5 leaders of the district. M Yunus from Bengkulu as cross check the results of the questionnaire that produces. Assessment data and data. Assessment data and data data and data data. Results The study demonstrates the role of individuals, the role of the organization and the role of management has contributed to the career development of non medical workers in Dr. M. Yunus from Bengkulu. Based on the results of research in terms of the role of individuals, non-medical personnel hospital needs to be increased awareness given in addition to medical personnel in the district. M. Yunus from Bengkulu should be more actively seeking information about career development. In the aspect of the role of management, leadership must be continuously supported and non medical labor in Dr M. Yunus Bengkulu and the leadership and is expected to continue to communicate the mission, policy, and information information in order to create increased. In the aspect of organizational role, Dr. M. Yunus from Bengkulu must provide training facilities and facilities that support the career development of non-medical personnel. In addition, it should be Dr. M. Yunus from Bengkulu should devise a special program to support the career development of non-medical personnel.Key words: individual roles, management role, organization roll, career development